International review of cytology : a survey of cell biology. - Jeon, Kwang W. (International review of cytology, 1997)
International Review of Cytology presents current advances and comprehensive reviews in cell biology-both plant and animal. Articles address structure and control of gene expression, nucleocytoplasmic interactions, control of cell development and differentiation, and cell transformation and growth. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research. Key Features * Transport of Glucose across the Blood-Tissue Barriers * The Role of Suppressors in Determining Host-Parasite Specificities in Plant Cells * Distribution and Functions of Platelet-Derived Growth Factors and Their Receptors during Embryogenesis * Adaptive Crystal Formation in Normal and Pathological Calcifications in Synthetic Calcium Phosphate and Related Biomaterials * The Biogenesis, Traffic, and Function of Cystic Fibrosis Transmembrane Conductance Regulator * Regulation of Phenylpropanoid Metabolism in Relation to Legnin Biosynthesis in Plants.